Determination of atomic diffusion coefficient via isochronal spark plasma sintering. (1st July 2018) - Li, X.X.; Yang, C.; Chen, T.; Fu, Z.Q.; Li, Y.Y.; Ivasishin, O.M.; Lavernia, E.J.
Abstract: During spark plasma sintering (SPS), it is widely argued that the densification mechanism of powder particles can be correlated with some specific physical quantities; however, an atomic diffusion coefficient D has yet to be derived. In this work, we report on the establishment of a framework, which can be used to derive the value of the D and further provide significant insight into the densification mechanisms that are active during powder sintering. We validate the framework by comparing the densification behavior of the atomized and milled Ti40.6 Zr9.4 Cu37.5 Ni9.4 Sn3.1 metallic glass powders during SPS, and clarifying the underlying densification mechanisms. Graphical abstract: We established a framework that can be used to derive a coefficient D and further correlate the as-derived D with the densification mechanism of powder particles during SPS. Correspondingly, the higher D for the milled Ti40.6 Zr9.4 Cu37.5 Ni9.4 Sn3.1 metallic glass powders determines the higher instantaneous densification rate ρ ̇ compared to the atomized counterparts. Unlabelled Image